Spontaneous partial resolution of autoimmune-mediated brain MRI abnormalities before immunotherapy in anti-metabotropic glutamate receptor 5 encephalitis: a case report - Chen, Jingjiong; Tang, Xin; Wang, Linran; Guo, Dandan; Cao, Li; Lu, Kaili (Frontiers in Immunology, 2025)
Anti-metabotropic glutamate receptor 5 (mGluR5) encephalitis is a rare autoimmune disorder characterized by varied neurological symptoms, often associated with limbic syndromes. We report the case of a 57-year-old female who presented with obvious ataxia, and then cognitive impairment and behavioral changes. MRI revealed cerebellar dentate nucleus and basal ganglia lesions with enhancement, which spontaneously regressed on follow-up imaging—a rare phenomenon in mGluR5 encephalitis. Diagnosis was confirmed by the presence of serum mGluR5 antibodies. Extensive evaluations excluded underlying malignancies. Immunotherapy, including corticosteroids and intravenous immunoglobulin, led to significant clinical and radiological improvement. This case highlights the unique cerebellar dentate nucleus and basal ganglia involvement and spontaneous partial reduction of lesions in mGluR5 encephalitis, expanding the clinical spectrum of this condition. Early recognition and immunotherapy are crucial for favorable outcomes. Further studies are needed to elucidate the mechanisms behind spontaneous partial lesion regression in autoimmune encephalitis.